2018
DOI: 10.1111/ecin.12718
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Motivational Crowding Out of Work Performance

Abstract: This paper shows that prior financial incentives induce a crowding‐out effect when incentives are discontinued. In our real‐effort experiment workers receive a piece rate before monetary incentives are substituted by a one‐time payment. In this case, workers' performance significantly drops when receiving the one‐time payment. The effect is driven by a fraction of men who reduce effort substantially, whereas women constantly perform well. We find that this motivational crowding‐out effect disappears when men d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Interestingly, subjects achieve a relatively high performance although the payment is not linked to performance. This is in line with the findings of Benndorf, Rau, and Sölch (2019). An explanation may be that subjects are bored and face low effort costs.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, subjects achieve a relatively high performance although the payment is not linked to performance. This is in line with the findings of Benndorf, Rau, and Sölch (2019). An explanation may be that subjects are bored and face low effort costs.…”
Section: Resultssupporting
confidence: 93%
“…The influence of motivation on performance has been found both in previous research [51][52][53][54][55] and in several experimental studies in the last 10 years. Significant impact was found for feedback [56] as well as changes in the payment scheme, when the fixed fee was changed for a fee per piece, the effect increased and vice versa-when the payment per piece was changed for a fixed fee, the effect decreased [57,58]. The studies also found a positive impact of involvement as well as autonomy on efficiency.…”
Section: Literature Reviewmentioning
confidence: 84%
“…With the intervention of financial incentives, people will be motivated to work to improve performance. Previous research found that people with boring and repeated assignment have higher performance when there is pay per performance incentives (Benndorf, Rau and Solch 2019). The individual sees as expectations of financial incentives, where their efforts in working unattractive task would be appreciated.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%